Diversity and the media - Metykova, Monika (Key concerns in media studies., 2016)
"Offers a concise and interdisciplinary overview of the relationship between diversity and media. Focusing on media regulation in democratic societies throughout, individual chapters explore how different conceptions of diversity relate to media audiences, media workforces, media outlets and media content. Drawing on research approaches grounded in the political economy of media, political communication, media economics and critical media industry studies, the book analyses a wide range of current and historical examples from the UK, the US and Europe"--Publisher's description.